Supercoil-induced Z-DNA formation within 5'-end of chicken myb proto-oncogene - Vlach, J; Dvorak, M; Bartunek, P; Pecenka, V; Travnicek, M; Sponar, J (Biochemical and biophysical research communications, 1989)
We have analyzed the recently sequenced and characterized 2.9 kb fragment derived from the 5'-end of chicken myb proto-oncogene with respect to structural perturbations induced by DNA supercoiling. Within the first intron a 50 bp sequence stretch was localized, starting approximately 450 nucleotides downstream from putative ATG initiation codon, which forms a non-B-DNA structure. Fine mapping with structural probes revealed the three adjacent regions with imperfect purine-pyrimidine alternation creating together relatively long Z-forming tract, parts of which may undergo a B-Z DNA transition at different superhelical densities.
Keywords: oxid osmičelý; Electrophoresis, Agar Gel; protoonkogenní proteiny c-myb; sekvence nukleotidů; Chickens; elektroforéza v agarovém gelu; Molecular Sequence Data; klonování DNA; molekulární sekvence - údaje; diethylpyrokarbonát; alkylace; Alkylation; plazmidy; zvířata; protoonkogenní proteiny; Proto-Oncogene Proteins c-myb; kur domácí; superhelikální DNA; Base Sequence; Codon; konformace nukleové kyseliny; kodon; Proto-Oncogene Proteins; Introns; Nucleic Acid Conformation; Animals; Cloning, Molecular; Plasmids; DNA, Superhelical; introny; Osmium Tetroxide; Diethyl Pyrocarbonate